Central American biomass burning smoke can increase tornado severity in the U.S. Issue 3 (13th February 2015) - Saide, P. E.; Spak, S. N.; Pierce, R. B.; Otkin, J. A.; Schaack, T. K.; Heidinger, A. K.; da Silva, A. M.; Kacenelenbogen, M.; Redemann, J.; Carmichael, G. R.
Abstract: Tornadoes in the Southeast and central U.S. are episodically accompanied by smoke from biomass burning in central America. Analysis of the 27 April 2011 historical tornado outbreak shows that adding smoke to an environment already conducive to severe thunderstorm development can increase the likelihood of significant tornado occurrence. Numerical experiments indicate that the presence of smoke during this event leads to optical thickening of shallow clouds while soot within the smoke enhances the capping inversion through radiation absorption. The smoke effects are consistent with measurements of clouds and radiation before and during the outbreak. These effects result in lower cloud bases and stronger low‐level wind shear in the warm sector of the extratropical cyclone generating the outbreak, two indicators of higher probability of tornadogenesis and tornado intensity and longevity. These mechanisms may contribute to tornado modulation by aerosols, highlighting the need to consider aerosol feedbacks in numerical severe weather forecasting. Key Points: First time smoke influence on tornado severity is shown for a real case study A new mechanism on how smoke can influence tornadoes is presented We show that aerosol effects should be considered in severe weather forecasts